Differences in natural bracing between early mature street trees of Norway maple (Acer platanoides L.) and small-leaved lime (Tilia cordata Mill. "Rancho"). Issue 2 (3rd April 2019) - Tothill, Ruth M.; Slater, Duncan
ABSTRACT: Included bark is considered a significant structural flaw in the crown of an amenity tree. However, recent research identifies natural bracing within the crowns of trees is associated with the formation of bark-included junctions lower down. To advance this research, differences in natural bracing between species and cultivars should be assessed. A survey of thirty early mature specimens of both Acer platanoides L. and Tilia cordata Mill. 'Rancho' was completed in 2017. These two tree types have similar rates of formation of bark-included junctions but reputably have differing failure rates. In these sixty trees, all major branch junctions from ground level to three metres were inspected and any associated natural braces categorised. Bark inclusions in the Norway maples were associated with fewer natural braces (44.4% association) and the trees contained a higher proportion of cup unions. In comparison, bark inclusions in the thirty lime cultivars were associated with more natural braces (78.3% association) and the trees contained a higher proportion of wide-mouthed bark inclusions. The differing forms and levels of self-shading in these two tree types are considered the key factors that explain the differences found in the survey. This finding informs better tree assessment and formative pruning programmes.